Resveratrol and Saccharin As Adherence Markers Discriminate Between Daily, Intermittent, or Non-consumption of Small-Quantity Lipid-Based Nutrient Supplements. (7th June 2021) - Zyba, Sarah; Weinborn, Valerie; Arnold, Charles; Morel, Fanny; Zeilani, Mamane; Mitchell, Alyson; Haskell, Marjorie
Abstract: Objectives: An objective adherence marker is needed to track consumption of nutrient supplements in nutrition intervention trials and programs targeted to young children and women of reproductive age in low-income countries. Here, resveratrol and saccharin are evaluated as adherence markers for tracking short-term intermittent or daily consumption of a small-quantity lipid-based nutrient supplement (SQ-LNS) in US women in a ten-day controlled feeding study. Methods: Sixty-three women were randomly assigned to receive daily for 10 d either: SQ-LNS containing trans -resveratrol (10 mg) and sodium saccharin (10 mg) (SQ-LNS/RS); 2) control SQ-LNS without the markers (SQ-LNS/C); or 3) alternating SQ-LNS/RS or SQ-LNS/C to simulate intermittent consumption. Urine concentrations of saccharin and trans -resveratrol-3-O-sulfate were measured in pooled urine samples collected 0–4 h post-consumption of the assigned SQ-LNS product on study days 4, 5, 9 and 10. Cutoff values were determined for urinary concentrations of each compound for classifying participants as consumers or non-consumers of SQ-LNS/RS. Then, participants were classified as daily, intermittent or non-consumers of SQ-LNS/RS based on their overall consumption pattern (number of days classified as a consumer during the 10-d period). Results: The cutoff value for urinary trans -resveratrol-3-O-sulfate (0.80 µmol/L) classified participants correctly as consumers or non-consumers in 97% of samples; the cutoff value for urinary saccharin (6.92 µmol/L) classified participants correctly in 93% of samples. Overall, 95% of daily, 95% of intermittent, and 100% of control group participants were classified correctly into their consumption pattern based on urinary trans -resveratrol-3-O-sulfate concentrations during the 10-d period; and 75% of daily, 95% of intermittent, and 100% of control participants were classified correctly based on urinary saccharin concentrations. Conclusions: The results suggest that urinary concentrations of saccharin and trans -resveratrol-3-O-sulfate may be useful for qualitative assessment of daily vs. intermittent vs. non-consumption of SQ-LNS; further work is needed to assess the usefulness of the markers in the intended target populations. Funding Sources: Bill & Melinda Gates Foundation